A Stein Criterion Via Divisors for Domains Over Stein Manifolds - Breaz, Daniel; Vâjâitu, Viorel (MATHEMATICA SCANDINAVICA, 2014)
It is shown that a domain $X$ over a Stein manifold is Stein if the following two conditions are fulfilled: a) the cohomology group $H^i(X,\mathscr{O})$ vanishes for $i ≥ 2$ and b) every topologically trivial holomorphic line bundle over $X$ admits a non-trivial meromorphic section. As a consequence we recover, with a different proof, a known result due to Siu stating that a domain $X$ over a Stein manifold $Y$ is Stein provided that $H^i(X,\mathscr{O})=0$ for $i ≥ 1$.